Excellence in college teaching and learning : classroom and online instruction - Henderson, George; Smith-Nash, Susan (Charles C Thomas Publisher, LTD, 2007)
This book will improve the quality of instruction that college students need. It makes numerous suggestions that must be tended to when teachers instruct students. For example, the authors speculate about ways teachers can present what may at times seem to be a mountain of information without burying students under it; why teachers must continually update their Internet skills; and whether courses are taught on campus or online, they should not be academic fluff or pedagogical gimmicks. Throughout the book the authors punctuate sentences and paragraphs with metaphors, similes, hyperboles, and.